Preparation method of POSS modified polyaspartic ester and polyurea coating

CN117777460BActive Publication Date: 2026-10-27SHENZHEN FEIYANG JUNYAN TECH DEV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311835393.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-27
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

[0004]上述聚脲型聚天门冬氨酸酯能够具有较高的耐磨性、强度和粘结性,可使用多种方式施工,在浇筑等表面形成光滑涂层,但目前仍存在聚天门冬氨酸酯的分子量小,分子中酯键含量高,与异氰酸酯反应之后制得的聚天门冬氨酸酯聚脲涂料与水接触角较低,疏水性及耐水性不佳的问题,同时防腐蚀性能有所欠缺

Benefits of technology

1、由于本申请采用氨基化笼型聚倍半硅氧烷对聚天门冬氨酸酯进行酯氨解反应液,在聚天门冬氨酸酯的冠状结构上通过化学接枝氨基化笼型聚倍半硅氧烷,从而改善了氨基化笼型聚倍半硅氧烷与聚天门冬氨酸酯型聚脲涂料的分散性和相容性,进而增强了涂料的耐候性、防腐蚀型和阻燃性,提高其疏水性和耐水性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004637457410000091
    Figure BDA0004637457410000091
  • Figure BDA0004637457410000101
    Figure BDA0004637457410000101
Patent Text Reader

Abstract

The application relates to the technical field of coatings, and particularly discloses a preparation method of POSS modified polyaspartic ester and polyurea coating. The preparation method of the POSS modified polyaspartic ester comprises the following steps: S1, amino-caged polysilsesquioxane is added into polyaspartic ester, after stirring, an alkali catalyst is added, and reaction is carried out for 5-16 hours; the mass ratio of the amino-caged polysilsesquioxane, the polyaspartic ester and the alkali catalyst is 1:2-3:0.01-0.01; S2, an extraction liquid is added into the product obtained in the step S1, the extraction liquid comprises ethyl acetate and water, after extraction, the upper solution is taken out and subjected to rotary evaporation. The method is simple in steps, easy to mass-produce, and the prepared POSS modified polyaspartic ester can be uniformly dispersed in a polyaspartic ester system, so that the coating has higher heat resistance, corrosion resistance, and certain hydrophobicity and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating technology, and more specifically, to a method for preparing POSS-modified polyaspartic acid ester and a polyurea coating. Background Technology

[0002] Polyaspartic acid ester resin is prepared by the Maillard addition method using aliphatic or alicyclic diamines or polyamines with maleic or fumarate esters. The secondary amine group of polyaspartic acid ester has lower reactivity than the hydroxyl group of general polyurethane resins, resulting in a faster reaction rate and a longer curing period. It does not require baking or heating for curing. Furthermore, polyaspartic acid ester has a small molecular weight and low viscosity, allowing for application without the need for solvents. Therefore, it is often combined with isocyanates to create environmentally friendly coatings. The coating can be applied by spraying, eliminating the need for specialized and expensive equipment compared to previous polyurea systems. It can be widely used for corrosion protection of outdoor steel structures, coating of petrochemical facilities requiring antistatic, thermal insulation, and corrosion protection, industrial coating of power equipment, protection of wind turbine towers and blades, decorative protection of concrete surfaces, tunnel renovation, and other fields.

[0003] In the prior art, Chinese invention patent application number [number missing] discloses a polyurea-type polyaspartic acid ester waterproof coating, which is composed of component A and component B. The raw materials for preparing component A include 90-110 parts of polyaspartic acid ester and 0-1 parts of additives by weight. The raw materials for preparing component B include 70-90 parts of polyisocyanate and 15-25 parts of solvent by weight.

[0004] The aforementioned polyurea-type polyaspartic ester has high wear resistance, strength, and adhesion, and can be applied in various ways to form a smooth coating on surfaces such as cast iron. However, it still has some drawbacks, such as the small molecular weight of polyaspartic ester, the high content of ester bonds in the molecule, the low water contact angle of polyaspartic ester polyurea coatings obtained after reacting with isocyanates, poor hydrophobicity and water resistance, and some lack of anti-corrosion performance. Summary of the Invention

[0005] To improve the hydrophobicity of polyaspartic ester polyurea coatings, this application provides a method for preparing POSS-modified polyaspartic ester and a polyurea coating.

[0006] In a first aspect, this application provides a method for preparing POSS-modified polyaspartic acid ester, employing the following technical solution: A method for preparing POSS-modified polyaspartic acid ester includes the following steps: S1. Add the aminated cage-type polysilsesquioxane to the polyaspartic acid ester, stir, add the alkaline catalyst, and react at 120-150℃ for 5-16h. The mass ratio of the aminated cage-type polysilsesquioxane, polyaspartic acid ester and alkaline catalyst is 1:(2-3):(0.01-0.01). S2. Add an extraction solution, which includes ethyl acetate and water, to the product obtained in step S1. After extraction, take the upper layer solution and perform rotary evaporation to obtain POSS-modified polyaspartic acid ester.

[0007] By adopting the above technical solution, cage-like polysilsesquioxane (POSS) is an inorganic-organic nanohybrid material with a three-dimensional spatial structure. With Si atoms as vertices, it forms a cage-like structure through alternating Si-O-Si bonds, with organic functional groups connected at the vertices. This structure combines the advantages of both inorganic and organic materials, exhibiting excellent characteristics in mechanical properties, thermal stability, chemical resistance, ultra-low dielectric constant, and biocompatibility. The process involves esterification and ammonolysis of polyaspartic acid ester with amino groups on the surface of the cage-like polysilsesquioxane to form O=CN bonds, thereby amination of the cage-like polysilsesquioxane and polyaspartic acid. The ester is chemically bonded, thereby chemically grafting the aminated cage-like polysilsesquioxane onto the crown structure of the polyaspartic ester. This results in POSS-modified polyaspartic ester coatings exhibiting superior heat resistance, corrosion resistance, and better hydrophobicity and flame retardancy compared to coatings prepared from conventional polyaspartic esters. Furthermore, the preparation method of POSS-modified polyaspartic ester utilizes chemical bonding to synthesize amide bonds, firmly binding the aminated cage-like polysilsesquioxane to the polyaspartic ester. This allows for better dispersibility of the aminated cage-like polysilsesquioxane within the polyaspartic ester, thus maximizing its performance.

[0008] The coating formed by this material exhibits a labyrinth effect and a certain degree of water repellency, significantly improving the coating's corrosion resistance. Furthermore, in the flame retardant field, due to the stable Si-O-Si structure, the aminated cage-like polysilsesquioxane forms a dense silica film at high temperatures. This effectively prevents the escape of small molecules and dripping of molten material after polymer decomposition, blocking oxygen and heat transfer to the polymer interior, thereby enhancing the coating's flame retardant properties.

[0009] Optionally, the aminated cage-type polysilsesquioxane is an aminopropylheptyl-cage-type polysilsesquioxane.

[0010] By adopting the above technical solution, aminopropylheptyl-cage polysilsesquioxane contains amino groups, which undergo ester ammonolysis with polyaspartic acid ester to improve the dispersibility of aminated cage polysilsesquioxane in polyaspartic acid ester, thereby increasing the weather resistance, flame retardancy and hydrophobicity of polyaspartic acid ester-type polyurea coatings.

[0011] Optionally, the polyaspartic ester is selected from any one of polyaspartic ester F420, polyaspartic ester F520, polyaspartic ester F220 and polyaspartic ester F330.

[0012] By adopting the above technical solutions, all types of polyaspartic acid can undergo ester-ammonolysis with aminated cage-type polysilsesquioxane to form a coating with excellent leveling, gloss, weather resistance, and water resistance.

[0013] Optionally, the stirring speed is 2000-3000 r / min and the stirring time is 2-3 h.

[0014] By adopting the above technical solution, the stirring speed and stirring time can ensure that the aminated cage-type polysilsesquioxane and polyaspartic acid ester are fully mixed and reacted.

[0015] Optionally, the alkaline catalyst is ammonia or a sodium hydroxide solution with a concentration of 0.2-1 mol / L.

[0016] By adopting the above technical solution and using ammonia or sodium hydroxide solution as an alkaline catalyst, the aminated cage-type polysilsesquioxane and polyaspartic acid ester can undergo an ester-ammonolysis reaction. The aminated cage-type polysilsesquioxane is grafted onto the polyaspartic acid ester, improving its dispersibility in polyaspartic acid ester-type polyurea coatings, thereby increasing the weather resistance, flame retardancy and hydrophobicity of the polyurea coatings.

[0017] Optionally, the mass ratio of ethyl acetate to water in the extract is 1:20-200.

[0018] Secondly, this application provides a polyurea coating, which adopts the following technical solution: A polyurea coating comprising the following steps: comprising the following raw materials in parts by weight: 8-12 parts of POSS modified polyaspartic acid ester, 75.6-84.4 parts of polyaspartic acid ester, 0.8-1.2 parts of defoamer, 0.8-1.2 parts of leveling agent and 6-10 parts of butyl ester solution.

[0019] By adopting the above technical solution, POSS-modified polyaspartic ester improves the dispersibility of aminated cage-type polysilsesquioxane and polyaspartic ester. Aminated cage-type polysilsesquioxane has good heat resistance and weather resistance. After being firmly bonded with polyaspartic ester, it improves the weather resistance of polyurea coating and gives the coating certain flame retardancy and hydrophobicity.

[0020] Optionally, the polyurea coating may further include 1-3 parts by weight of modified graphene oxide.

[0021] By adopting the above technical solutions, graphene oxide, with its layered structure, is added to coatings and stacked layer by layer, forming a more complex anti-diffusion erosion path. The physical barrier effect of graphene oxide itself is also more obvious, resulting in better performance of the modified coating. When coated on metal and other substrates, it enhances the corrosion resistance of the substrate. Graphene oxide also optimizes the structure of the resin by forming chemical bonds, improving the neatness of the molecular arrangement, reducing structural defects in the coating, and forming a tight protective film. This further enhances the coating's impermeability, adhesion, and impact resistance. The layered structure of graphene oxide can improve the airtightness of the coating, increasing the pathway for oxygen to pass through the coating, better isolating the material from external heat and oxygen, and improving the temperature resistance of the film.

[0022] Optionally, the modified graphene oxide undergoes the following pretreatment: Trisilyl phenyl-cage polysilsesquioxane was added to N-methylpyrrolidone and stirred to dissolve. Nano-silica was added and ultrasonically dispersed for 20-30 minutes. Graphene oxide was added and impregnated under negative pressure for 10-20 minutes. The mixture was then filtered and dried. The mass ratio of graphene oxide, trisilyl phenyl-cage polysilsesquioxane, and nano-silica was 1:0.2-0.4:0.05-0.1.

[0023] By adopting the above technical solution, trisilyl phenyl-cage-type polysilsesquioxane, due to its rigid aromatic hydrocarbon structure and excellent thermal stability, is widely used in high-temperature and flame-retardant applications. It contains active -Si-OH groups, allowing it to disperse in most organic solvents. Dissolving it with NMP, the dissolved trisilyl phenyl-cage-type polysilsesquioxane, under negative pressure, allows the solvent to penetrate into the spaces between graphene oxide particles. The silanol groups on the trisilyl phenyl-cage-type polysilsesquioxane can form hydrogen bonds with the hydroxyl groups on the graphene oxide, reducing graphene agglomeration, lowering its rigidity, and increasing its toughness. This method improves the impact resistance of the coating by adding nano-silica to dissolved trisilyl phenyl-cage polysilsesquioxane. The trisilyl phenyl-cage polysilsesquioxane molecule contains silicon-oxygen bonds and silanol groups that are highly similar to those of silica. These bonds interact with the silicon-oxygen bonds and hydroxyl groups on the surface of the nano-silica, allowing the nano-silica to be uniformly dispersed in the trisilyl phenyl-cage polysilsesquioxane. This results in the nano-silica being tightly encapsulated by the trisilyl phenyl-cage polysilsesquioxane, improving the wear resistance and corrosion resistance of graphene oxide, and enhancing the density and erosion resistance of the coating.

[0024] Thirdly, this application provides a POSS-modified anti-corrosion aspartic polyurea coating, which adopts the following technical solution: A POSS-modified anti-corrosion aspartic polyurea coating includes a primer layer and a topcoat layer arranged sequentially from bottom to top. The topcoat layer is formed by spraying a mixture of polyurea coating and isocyanate curing agent at a mass ratio of 100:96-100.

[0025] By adopting the above technical solution and using coatings containing POSS-modified polyaspartic acid ester, the introduction of aminated POSS is beneficial to improving the corrosion resistance and weather resistance of the coating, and also imparts certain flame retardancy and hydrophobicity to the coating.

[0026] In summary, this application has the following beneficial effects: 1. Because this application uses aminated cage-type polysilsesquioxane to perform ester ammonolysis reaction on polyaspartic acid ester, the aminated cage-type polysilsesquioxane is chemically grafted onto the crown structure of polyaspartic acid ester, thereby improving the dispersibility and compatibility of the aminated cage-type polysilsesquioxane with polyaspartic acid ester-type polyurea coating, thereby enhancing the coating's weather resistance, corrosion resistance and flame retardancy, and improving its hydrophobicity and water resistance.

[0027] 2. In this application, aminopropylheptyl-cage polysilsesquioxane is preferably used to chemically graft polyaspartic acid ester, which can improve the heat resistance of polyurea coatings.

[0028] 3. In this application, it is preferred to add modified graphene oxide to the polyurea coating. The graphene oxide is modified by using trisilyl phenyl-cage polysilsesquioxane and nano silica to increase the dispersibility of graphene oxide in the polyurea coating, enhance the density of the coating, and further improve the corrosion resistance, weather resistance and impact resistance of the coating. Detailed Implementation

[0029] The following embodiments provide a further detailed description of this application.

[0030] Preparation Examples of Modified Graphene Oxide 1-4 In the preparation example, the trisilyl alcohol phenyl-cage-type polysilsesquioxane was selected from Forsmann Technology (Beijing) Co., Ltd., catalog number 9502013; the nano silica was selected from Jingrui Guangzhou New Materials Co., Ltd., with a particle size of 10 nm; and the graphene oxide was selected from Xianfeng Nano, catalog number 100602.

[0031] Preparation Example 1: 9g of trisilyl phenyl-cage polysilsesquioxane was added to N-methylpyrrolidone and stirred to dissolve, resulting in a solution with a concentration of 0.9g / 10mL. Nano-silica was added and ultrasonically dispersed at 500W for 20min. Graphene oxide was added and impregnated at -0.03MPa for 20min. The solution was then filtered and dried. The mass ratio of graphene oxide, trisilyl phenyl-cage polysilsesquioxane, and nano-silica was 1:0.4:0.1.

[0032] Preparation Example 2: 6g of trisilyl phenyl-cage polysilsesquioxane was added to N-methylpyrrolidone and stirred to dissolve, resulting in a solution with a concentration of 0.6g / 10mL. Nano-silica was added and ultrasonically dispersed at 500W for 10min. Graphene oxide was added and impregnated at -0.05MPa for 10min. The solution was then filtered and dried. The mass ratio of graphene oxide, trisilyl phenyl-cage polysilsesquioxane, and nano-silica was 1:0.2:0.05.

[0033] Preparation Example 3: The difference from Preparation Example 1 is that an equal amount of deionized water is used instead of trisilyl phenyl-cage polysilsesquioxane.

[0034] Preparation Example 4: The difference from Preparation Example 1 is that no nano-silica was added. Example

[0035] In the examples, aminopropylhepta-cage polysilsesquioxane was selected from Xi'an Qiyue Biotechnology, ethyl acetate from Shandong Taixi Chemical Co., Ltd., polyaspartic acid ester from Shenzhen Feiyang Junyan New Material Co., Ltd. (model F520), and defoamer from Evonik Industries AG (Germany) (model [missing information]). Airex900, the leveling agent is selected from BYK-300 by BYK Chemical AG, Germany. Example 1: A method for preparing POSS-modified polyaspartic acid ester, comprising the following steps: S1. Aminated cage-type polysilsesquioxane was added to polyaspartic acid ester and stirred at 2000 r / min for 3 h. Then, an alkaline catalyst was added and the mixture was reacted at 120 °C for 16 h. The mass ratio of aminated cage-type polysilsesquioxane, polyaspartic acid ester and alkaline catalyst was 1:3:0.01. The aminated cage-type polysilsesquioxane was aminopropylheptyl-cage-type polysilsesquioxane with a particle size of 3 nm. The alkaline catalyst was a 1 mol / L sodium hydroxide solution. S2. Add an extraction solution to the product obtained in step S1. The extraction solution includes ethyl acetate and water. After extraction, take the upper layer solution and perform rotary evaporation to obtain POSS modified polyaspartic acid ester. The mass ratio of ethyl acetate to water is 1:20. The rotary evaporation temperature is 80℃ and the time is 20min.

[0036] Example 2: A method for preparing POSS-modified polyaspartic acid ester, comprising the following steps: S1. Aminated cage-type polysilsesquioxane was added to polyaspartic acid ester and stirred at 3000 r / min for 2 h. Then, an alkaline catalyst was added and the mixture was reacted at 150 °C for 5 h. The mass ratio of aminated cage-type polysilsesquioxane, polyaspartic acid ester and alkaline catalyst was 1:3:0.1. Aminated cage-type polysilsesquioxane was aminopropylheptyl-cage-type polysilsesquioxane with a particle size of 1 nm. The alkaline catalyst was a 0.2 mol / L sodium hydroxide solution. S2. Add an extraction solution to the product obtained in step S1. The extraction solution includes ethyl acetate and water. After extraction, take the upper layer solution and perform rotary evaporation to obtain POSS modified polyaspartic acid ester. The mass ratio of ethyl acetate to water is 1:200. The rotary evaporation temperature is 60℃ and the time is 50min.

[0037] Example 3: A method for preparing POSS-modified polyaspartic acid ester, comprising the following steps: S1. Aminated cage-type polysilsesquioxane was added to polyaspartic acid ester and stirred at 2500 r / min for 2.5 h. Then, an alkaline catalyst was added and the mixture was reacted at 140 °C for 8 h. The mass ratio of aminated cage-type polysilsesquioxane, polyaspartic acid ester and alkaline catalyst was 1:2:0.01. The aminated cage-type polysilsesquioxane was aminopropylheptyl-cage-type polysilsesquioxane with a particle size of 1 nm. The alkaline catalyst was a sodium hydroxide solution with a concentration of 0.6 mol / L. S2. Add an extraction solution to the product obtained in step S1. The extraction solution includes ethyl acetate and water. After extraction, take the upper layer solution and perform rotary evaporation to obtain POSS modified polyaspartic acid ester. The mass ratio of ethyl acetate to water is 1:120. The rotary evaporation temperature is 70℃ and the time is 40min.

[0038] Example 4: A method for preparing POSS-modified polyaspartic acid ester, comprising the following steps: S1. Aminated cage-type polysilsesquioxane was added to polyaspartic acid ester and stirred at 2500 r / min for 3 h. Then, an alkaline catalyst was added and the mixture was reacted at 130 °C for 12 h. The mass ratio of aminated cage-type polysilsesquioxane, polyaspartic acid ester and alkaline catalyst was 1:2:0.1. Aminated cage-type polysilsesquioxane was aminopropylheptyl-cage-type polysilsesquioxane with a particle size of 1 nm. The alkaline catalyst was a sodium hydroxide solution with a concentration of 0.8 mol / L. S2. Add an extraction solution to the product obtained in step S1. The extraction solution includes ethyl acetate and water. After extraction, take the upper layer solution and perform rotary evaporation to obtain POSS modified polyaspartic acid ester. The mass ratio of ethyl acetate to water is 1:160. The rotary evaporation temperature is 80℃ and the time is 50min.

[0039] Example 5: A polyurea coating comprising the following raw materials in parts by weight: 10 kg of POSS-modified polyaspartic acid ester prepared in Example 1, 80 kg of polyaspartic acid ester F520, 1 kg of defoamer, 1 kg of leveling agent, and 8 kg of butyl ester solution. The polyurea coating is prepared by mixing POSS-modified polyaspartic acid ester, polyaspartic acid ester F520, defoamer, leveling agent, and butyl ester solution evenly to obtain the polyurea coating.

[0040] Example 6: A polyurea coating, which differs from Example 5 in that the POSS-modified polyaspartic acid ester is prepared according to Example 2.

[0041] Example 7: A polyurea coating, which differs from Example 5 in that the POSS-modified polyaspartic acid ester is prepared according to Example 3.

[0042] Example 8: A polyurea coating, which differs from Example 5 in that the POSS-modified polyaspartic acid ester is prepared according to Example 4.

[0043] Example 9: A polyurea coating, which differs from Example 5 in that the raw materials of the polyurea coating also include 3 kg of modified graphene oxide, which was prepared by Preparation Example 1.

[0044] Example 10: A polyurea coating, which differs from Example 5 in that the raw materials of the polyurea coating also include 1 kg of modified graphene oxide, which is prepared from Preparation Example 2.

[0045] Example 11: A polyurea coating, which differs from Example 5 in that the raw materials of the polyurea coating also include 3 kg of modified graphene oxide, which is prepared from Preparation Example 3.

[0046] Example 12: A polyurea coating, which differs from Example 5 in that the raw materials of the polyurea coating also include 3 kg of modified graphene oxide, which was prepared by Preparation Example 4.

[0047] Application Example 13: A polyurea coating, which differs from Example 5 in that the raw materials of the polyurea coating also include 3 kg of graphene oxide, which is selected from Xianfeng Nano, with the product number 100602.

[0048] Comparative Example Comparative Example 1: A polyurea coating, which differs from Example 5 in that an equal amount of polyaspartic ester F520 is used instead of the POSS-modified polyaspartic ester prepared in Example 1.

[0049] Application examples Application Example 1: A POSS modified anti-corrosion aspartic polyurea coating includes a primer layer and a topcoat layer arranged sequentially from bottom to top. The primer layer is made by applying epoxy paint, which is a zinc-rich primer, model Evante P5160, and the primer layer thickness is 30μm. The topcoat is prepared by spraying a mixture of polyurea coating prepared in Example 5 and isocyanate curing agent at a mass ratio of 100:96 onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0050] Application Example 2: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by uniformly mixing the polyurea coating prepared in Example 6 with the isocyanate curing agent at a mass ratio of 100:96 and then spraying it onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0051] Application Example 3: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by uniformly mixing the polyurea coating prepared in Example 7 with the isocyanate curing agent at a mass ratio of 100:96 and then spraying it onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0052] Application Example 4: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by uniformly mixing the polyurea coating prepared in Example 8 with the isocyanate curing agent at a mass ratio of 100:96 and then spraying it onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0053] Application Example 5: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by spraying the polyurea coating prepared in Example 9 and the isocyanate curing agent at a mass ratio of 100:96 onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0054] Application Example 6: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by spraying the polyurea coating prepared in Example 10 and the isocyanate curing agent on the primer layer after being mixed evenly at a mass ratio of 100:96. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the thickness of the topcoat layer is 80μm.

[0055] Application Example 7: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by uniformly mixing the polyurea coating prepared in Example 11 with the isocyanate curing agent at a mass ratio of 100:96 and then spraying it onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0056] Application Example 8: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by uniformly mixing the polyurea coating prepared in Example 12 with the isocyanate curing agent at a mass ratio of 100:96 and then spraying it onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0057] Application Example 9: A POSS modified anti-corrosion aspartic polyurea coating, the topcoat layer is prepared by spraying the polyurea coating prepared in Example 13 and the isocyanate curing agent at a mass ratio of 100:96 onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100. The thickness of the topcoat layer is 80μm.

[0058] Application Example 10: A POSS modified anti-corrosion aspartic polyurea coating, which differs from Application Example 1 in that the topcoat layer is prepared by spraying a mixture of polyurea coating prepared in Comparative Example 1 and isocyanate curing agent at a mass ratio of 100:96 onto the primer layer. The isocyanate curing agent is selected from HDI trimer, which is selected from Shenzhen Feiyang Junyan, model HT100, and the topcoat layer thickness is 80μm.

[0059] Performance testing The POSS-modified anti-corrosion aspartic polyurea coating was prepared according to the method in the application example, and the various properties of the coating were tested according to the following method. The test results are recorded in Table 1.

[0060] 1. Salt spray resistance: Tested in accordance with GB / T 1771-2007 "Determination of resistance to neutral salt spray of paints and varnishes".

[0061] 2. Aging resistance: Tested according to GB / T 16777-2008 "Test Methods for Waterproof Coatings for Buildings". 3. Surface contact angle: The test shall be conducted in accordance with the 16th test of the coating contact angle in GB / T 13448-2019 "Test Methods for Color Coated Steel Sheets and Strips".

[0062] 4. Flame retardancy: Tested in accordance with GB / T 12441-2018 "Decorative Fire-retardant Coatings" and GB / T 8624-2012 "Classification of Burning Performance of Building Materials and Products".

[0063] 5. Heat resistance: Tested in accordance with GB / T 1735-2009 "Determination of heat resistance of paints and varnishes".

[0064] 6. Impact resistance: Tested according to GB / T 1732-1993 "Test Method for Impact Resistance of Coating Film".

[0065] 7. Abrasion resistance (750g / 1000r): Tested according to GB / T 1768-2996 "Determination of abrasion resistance of paints and varnishes - Rotary rubber grinding wheel method".

[0066] Table 1 Combining the data from Application Examples 1-9 and Table 1, Application Examples 1-4 used the polyurea coatings prepared in Examples 5-8, respectively. The polyurea coatings in Examples 5-8 contained the POSS-modified polyaspartic acid ester prepared in Examples 1-4. The data in Table 1 show that the topcoat layers prepared in Application Examples 1-4 have a large contact angle with water, exhibiting good hydrophobic properties, achieving flame retardancy rating A, and an impact resistance of 50 kg·cm². -1It exhibits excellent resistance to salt spray and aging.

[0067] Compared with Application Example 1, Application Examples 5 and 6 also added modified graphene oxide to the polyurea coating that forms the topcoat layer. As shown in Table 1, the coatings prepared in Application Examples 5 and 6 still have excellent weather resistance, flame retardancy and hydrophobicity, and the impact resistance is increased and the wear resistance is further improved.

[0068] In Application Example 7, the polyurea coating prepared in Example 11 was used. The modified graphene oxide added to the polyurea coating in Example 11 was prepared in Preparation Example 3. Compared with Application Example 1, the impact resistance, hydrophobicity and weather resistance of the topcoat layer prepared in Application Example 7 did not change much, but its abrasion resistance decreased slightly.

[0069] In Application Example 8, the polyurea coating prepared in Example 12 was used, wherein the modified graphene oxide was prepared in Preparation Example 4. Compared with Application Example 1, the topcoat layer prepared in Application Example 8 had reduced impact resistance and abrasion resistance.

[0070] In Application Example 9, the polyurea coating prepared in Example 13 was used, which contained unmodified graphene oxide. Compared with Application Example 1, the paint-free layer prepared in Application Example 9 had poor compatibility of graphene oxide in the coating, resulting in a decrease in its impact resistance and abrasion resistance.

[0071] In Application Example 10, a topcoat layer was formed using polyaspartic acid ester and isocyanate curing agent. Compared with Application Example 1, it had a lower contact angle and reduced weather resistance and flame retardancy.

[0072] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing POSS-modified polyaspartic acid ester, characterized in that, Includes the following steps: S1. Add the aminated cage-type polysilsesquioxane to the polyaspartic acid ester, stir, add the alkaline catalyst, and react at 120-150℃ for 5-16h. The mass ratio of the aminated cage-type polysilsesquioxane, polyaspartic acid ester and alkaline catalyst is 1:(2-3):(0.01-0.1). S2. Add an extraction solution, which includes ethyl acetate and water, to the product obtained in step S1. After extraction, take the upper layer solution and perform rotary evaporation to obtain POSS-modified polyaspartic acid ester.

2. The method for preparing POSS-modified polyaspartic acid ester according to claim 1, characterized in that: The aminated cage-type polysilsesquioxane is aminopropylheptyl-cage-type polysilsesquioxane.

3. The method for preparing POSS-modified polyaspartic acid ester according to claim 1, characterized in that: The polyaspartic ester is selected from any one of polyaspartic ester F420, polyaspartic ester F520, polyaspartic ester F220 and polyaspartic ester F330.

4. The method for preparing POSS-modified polyaspartic acid ester according to claim 1, characterized in that: The stirring speed is 2000-3000 r / min, and the stirring time is 2-3 h.

5. The method for preparing POSS-modified polyaspartic acid ester according to claim 1, characterized in that: The alkaline catalyst is ammonia or a sodium hydroxide solution with a concentration of 0.2-1 mol / L.

6. The method for preparing POSS-modified polyaspartic acid ester according to claim 1, characterized in that: The mass ratio of ethyl acetate to water in the extract is 1:20-200.

7. A POSS-modified anti-corrosion aspartic polyurea coating, comprising a primer layer and a topcoat layer arranged sequentially from bottom to top, characterized in that, The topcoat layer is formed by spraying a mixture of polyurea coating and isocyanate curing agent at a mass ratio of 100:96-100. The polyurea coating contains POSS-modified polyaspartic acid ester prepared by the preparation method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Modified polyaspartate polyurea coating as well as preparation method and application thereof

    CN110373099A

  • Primer-topcoat coating and preparation method thereof

    CN115873483A